2001
DOI: 10.1016/s0896-6273(01)00247-1
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Cannabinoids Mediate Retrograde Signals from Depolarized Postsynaptic Neurons to Presynaptic Terminals

Abstract: Endogenous cannabinoids are considered to function as diffusible and short-lived modulators that may transmit signals retrogradely from postsynaptic to presynaptic neurons. To evaluate this possibility, we have made a paired whole-cell recording from cultured hippocampal neurons with inhibitory synaptic connections. In about 60% of pairs, a cannabinoid agonist greatly reduced the release of the inhibitory neurotransmitter GABA from presynaptic terminals. In most of such pairs but not in those insensitive to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
614
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 753 publications
(646 citation statements)
references
References 46 publications
29
614
0
3
Order By: Relevance
“…When restricting their measurements to endocannabinoid-sensitive synaptic connections, found a maximum inhibition during hippocampal DSI close to 90%. A similar value was obtained from paired recordings in the cerebellum (Diana et al, 2002;Figure 2b), whereas in hippocampal cultured cells DSI reaches a somewhat smaller value (about 75% in DSI sensitive pairs: Ohno-Shosaku et al, 2001). In slices, these values correspond to the inhibition obtained with saturating concentration of a cannabinoid exogenous agonist, showing that standard DSI induction protocols are able to saturate presynaptic CBIRs.…”
Section: Expression Mechanisms Of Dsi/dsesupporting
confidence: 74%
See 1 more Smart Citation
“…When restricting their measurements to endocannabinoid-sensitive synaptic connections, found a maximum inhibition during hippocampal DSI close to 90%. A similar value was obtained from paired recordings in the cerebellum (Diana et al, 2002;Figure 2b), whereas in hippocampal cultured cells DSI reaches a somewhat smaller value (about 75% in DSI sensitive pairs: Ohno-Shosaku et al, 2001). In slices, these values correspond to the inhibition obtained with saturating concentration of a cannabinoid exogenous agonist, showing that standard DSI induction protocols are able to saturate presynaptic CBIRs.…”
Section: Expression Mechanisms Of Dsi/dsesupporting
confidence: 74%
“…In addition hippocampal DSI was soon shown to be absent in CB1R-deficient mice . In a short period of time, the endocannabinoid-and CB1R-related nature of DSI has been confirmed in the hippocampus and extended to several systems: for GABAergic synapses onto cerebellar Purkinje cells (Kreitzer & Regehr, 2001b;Diana et al, 2002;Yoshida et al, 2002;Figure 2a), cultured rat hippocampal neurons (Ohno-Shosaku et al, 2001), hippocampal dentate granule cells in particular pathological conditions (Chen et al, 2003), cortical pyramidal cells (Trettel & Levine, 2003) and neurons of the substantia nigra (Yanovsky et al, 2003).…”
Section: Dsi and Dsementioning
confidence: 93%
“…Based on this anatomical relationship between FAAH and CB 1 expression, we predicted that endocannabinoids may act as retrograde signaling molecules at synapses in the brain (Egertová et al, 1998;Elphick and Egertová , 2001) and experimental studies on the hippocampus and cerebellar cortex have proved that this hypothesis was correct (Kreitzer and Regehr, 2001a,b;Maejima et al, 2001a,b;Ohno-Shosaku et al, 2001;). Therefore, it seems likely that endocannabinoids may also act as retrograde messengers at synapses in the many regions of the brain that we describe here where "complementary" expression of FAAH and CB 1 occurs, which include the olfactory cortex, amygdala, dentate gyrus, transitional cortex and neocortex.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, and Ohno-Shosaku et al (2001) showed that endocannabinoids mediate a retrograde signal from depolarized hippocampal pyramidal cells to presynaptic GABAergic axon terminals that causes suppression of inhibitory input (depolarization-induced suppression of inhibition or DSI). Similarly, Kreitzer and Regehr (2001a) reported that depolarization-induced suppression of excitation (DSE) in the cerebellar cortex is mediated by a retrograde endocannabinoid signal from depolarized Purkinje cells to presynaptic glutamatergic parallel fibers.…”
mentioning
confidence: 99%
“…An interesting mechanism, known as depolarization-induced suppression of inhibition (DSI), allows Purkinje cells to downregulate GABA release through the retrograde release of endocannabinoids that activate presynaptic cannabinoid receptors (CB1) located in GABAergic interneurons. After the initial stimulation, CB1 receptor activation reduces both probability of release and the overall synaptic efficacy for tens of seconds [112][113][114][115][116] (Figure 1c, d). Duguid and Smart 102 have recently identified a novel long-lasting mechanism (several minutes) termed depolarizationinduced potentiation of inhibition (DPI), which follows the termination of DSI and implies the potentiation of GABA release, reviewed in Tzingounis and Nicoll 117 (Figure 1c).…”
Section: Presynaptic Ltp Dependent Of Presynaptic Nmda Receptorsmentioning
confidence: 99%